Family diversity : a South African perspective focusing on Whites in Grahamstown - Ziehl, Susan C (Rhodes University, Faculty of Humanities, Department of Sociology, 1998)
Drawing on developments in the field of family history and studies of families in contemporary settings, the study addresses the question of explaining variations in household patterns. Its empirical basis is a survey of White households in Grahamstown. The surveyed population was broken down in terms of class (occupation) and culture (language) and analyses conducted to determine if there are any statistically significant relationships between these variables and the tendency to reside in particular household structures. The question of 'family ideology' was also addressed as an attempt was made to uncover subjects' views on a variety of family-related issues. On the basis of the research results, a model of the relationship between class, culture and household structure was developed. Its application to a comparison of Black and White household structures in South Africa as well as the United States, is discussed. Finally, attempts at redefining the family are addressed and a new definition of the family proposed.
Keywords: Families -- History -- Research; Families -- South Africa -- Grahamstown; Families Families -- Research -- South Africa